KNOWLEDGE OF HEALTH COMMUNICATION AND EDUCATION ABOUT DIABETES AMONG VILLAGE HEALTH WORKERS IN VU THU DISTRICT, THAI BINH PROVINCE IN 2020 (Vietnam Journal of Community Medicine, 2021)
Objective: Describe knowledge of health communication and education about diabetes among village health workers in Vu Thu district, Thai Binh province in 2020. Subjects: Village health workers in the communes of Vu Thu district, Thai Binh province. Method: the epidemiological method described through the cross-sectional investigation. Results: Percentage of village health workers were more female than men (84.4% and 16.6%); Percentage of subjects who believed that the main content that needs counseling on diabetes prevention was about reasonable diet (81.6%); Number of subjects choosing health counseling as the best form of communication about diabetes accounted the highest percentage.
Keywords: Village Health Worker, diabetes, health communication and education; knowledge